The Teachersâ Strategy on Studentsâ Communicative Ability Action Research - Suparman, Suparman (PALAPA: Jurnal Studi Keislaman dan Ilmu Pendidikan, 2018)
The study  aimed to find out the studentsâ communicative ability and how far the studentsâ improvement in communicative ability after getting the teaching and learning by using the appropriate teachersâ strategy. It was the communicative strategy to solve the problem of how is the communicative ability and how does the communicative strategy improve the communicative ability of the students. The research was designed in  a classroom  action research which was done on three cycles. The practicum was performed in class eight grade 8B of MTs.Yaqin 2 Pemondah which had 34 learners. During the practice the main area  taught was English using useful strategy to help the students in improving their communicative ability. The finding of the study on cycle one was 91.18%, meanwhile the hypothesis acceptance was 75 %. It was also happened on  cycle two and three. According to the gained data on cycle two, the studentsâ communicative ability reached 97,06%, and 100 % on cycle three. The gaining of the improvement of the studentsâ communicative ability reached more than 81.18% on cycle one, on cycle two reached up to 87.06%, and on cycle three reached up to 90%. So that the application of the teachersâ strategy in teaching and learning process may increase the studentsâ communicative ability.